Quadruple overlapping autoimmune diseases manifested as sarcoidosis with mediastinal lymphadenopathy: a case report - Li, Mengjie; Wang, Huan; Li, Cuiping; Su, Linming; Zhu, Jian (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
We present a rare case of a 55-year-old female patient with quadruple overlapping autoimmune diseases, including vitiligo, autoimmune hypothyroidism, ulcerative colitis, and sarcoidosis with mediastinal lymphadenopathy. The patient had been suffering from vitiligo since 2003 and was diagnosed with autoimmune hypothyroidism and ulcerative colitis through thyroid ultrasound and colonoscopy, respectively. After physical examination, mediastinal lymph nodes enlargement was detected, and sarcoidosis was diagnosed through ultrasound bronchoscope-guided transbronchial needle aspiration (EBUS-TBNA), which is a quadruple overlapping sign of autoimmune disease of sarcoidosis that has not been reported previously. The patient was treated with oral Chinese medicine for leukoplakia, oral levothyroxine sodium tablets to control thyroid function, and Chinese medicine enema for colitis, with intermittent treatment for 2 years. Prednisone acetate was administered for 1 month to reduce the size of the enlarged lymph nodes. Our case highlights the importance of considering sarcoidosis as a potential diagnosis in patients with autoimmune diseases who present with mediastinal lymphadenopathy.